Student Grade Input Information System Using Waterfall Method with Web-Based Student Attendance Data Analysis Feature (Case Study: SDN 064037 Medan Tembung) - Siregar, Sarmaia; Donni Lesmana Siahaan, Muhammad; Herdianto (Cattleya Darmaya Fortuna, 2025)
The development of information technology in the digital era requires educational institutions to adopt web-based information systems to improve the efficiency of data management. The process of entering grades and attendance that is still carried out manually has the potential to cause recording errors and delays in reporting. This research aims to design and build a web-based student score input information system with the Waterfall development method, and is equipped with a student attendance data analysis feature. This study was conducted at SDN 064037 Medan Tembung using observation, interview, and literature study methods. The development results show that the system built is multiuser and supports a secure and structured digital value input, attendance, and reporting process. This system makes it easy for teachers and admins to access and manage student data in real-time, accurate, and efficient manners.